Ultraviolet light induces increased T cell activation in lupus-prone mice via type I IFN-dependent inhibition of T regulatory cells. (September 2019) - Wolf, Sonya J.; Estadt, Shannon N.; Theros, Jonathan; Moore, Tyson; Ellis, Jason; Liu, Jianhua; Reed, Tamra J.; Jacob, Chaim O.; Gudjonsson, Johann E.; Kahlenberg, J. Michelle
Abstract: Ultraviolet (UV) light is a known trigger of skin and possibly systemic inflammation in systemic lupus erythematosus (SLE) patients. Although type I interferons (IFN) are upregulated in SLE skin after UV exposure, the mechanisms to explain increased UVB-induced inflammation remain unclear. This paper compares the role of type I IFNs in regulating immune cell activation between wild-type and lupus-prone mice following UVB exposure. 10-week old female lupus-prone (NZM2328), wild-type (BALB/c) and iNZM mice (lack a functional type I IFN receptor on NZM2328 background) were treated on their dorsal skin with 100 mJ/cm 2 of UVB for 5 consecutive days. Following UVB treatment, draining lymph node cell populations were characterized via flow cytometry and suppression assays; treated skin was examined for changes in expression of type I IFN genes. Only NZM2328 mice showed an increase in T cell numbers and activation 2 weeks post UVB exposure. This was preceded by a significant increase in UVB-induced type I IFN expression in NZM2328 mice compared to BALB/c mice. Following UVB exposure, both BALB/c and iNZM mice demonstrated an increase in functional T regulatory (TReg ) cells; however, this was not seen in NZM2328 mice. These data suggest a skewed UVB-mediated T cell response in lupus-prone mice where activation of T cells is enhanced secondary to a type I IFN-dependent suppression of TReg cells. Thus, we propose type I IFNs are important for UVB-induced inflammation in lupus-prone mice and may be an effective target for prevention of UVB-mediated flares. Highlights: Interferon responses to UVB are greater in lupus prone mice. UVB induces TREG production to restrain T cell activation in wild type mice. UVB induces T cell activation in lupus-prone mice secondary to inhibition of TREGs . Type I IFN is required for TREG inhibition in lupus-prone mice.